University students' perceptions of using TikTok in education: a preliminary study / Nur Ilianis Adnan and Berlian Nur Morat - Adnan, Nur Ilianis; Morat, Berlian Nur (Universiti Teknologi MARA, Pulau Pinang, 2022)
The number of young adults using various applications is increasing. Life in the 21st century requires people to constantly familiarize themselves with newly invented technologies that facilitate many aspects of life, including education. To this aim, some students choose to use the TikTok application. Students' perceptions of using TikTok in education have yet to be explored. The present questionnaires with 111 university students aim to explore two research questions: (1) What are the university students' experiences of using TikTok? and (2) What are the university students' perceptions of using TikTok in education? The results are presented in two parts according to the research objectives. The first part relates to students' experiences of using TikTok which focuses on the usage of TikTok and the difficulties they encountered. Five themes emerged from the question related to difficulties: privacy issues, technical difficulties, concerns about video content, lack of skills, and hindrance to learning. The second part of the findings focuses on learners' perceptions on the use of TikTok in education and the benefits of TikTok in learning. The latter revealed three main themes: entertainment, improving English skills and providing learning resources. These insights into students' perceptions of TikTok use in education can guide teachers and learners, as well as policymakers, in optimizing the use of TikTok in education.